Variations on A-Browder-Type Theorems - Berkani, Mohammed; Kachad, Mohammed; Zariouh, Hassan; Zguitti, Hassane (Sarajevo Journal of Mathematics, 2024)
We introduce and we study the new spectral properties (SBw), (SBaw), (SBab) and (SBb). Among other results, we show that if T is a bounded linear operator acting on a Banach space X, then T possesses property (SBb) if and only if T possesses property (b) and Π^0(T)=Π_a(T). 2010 Mathematics Subject Classification. Primary 47A53, 47A10, 47A11.